Penerapan Program Perawatan Spiritual untuk Menurunkan Depresi pada Pasien Leukemia - Rosliany, Nia; Irawaty, Dewi; Maria, Riri (Jurnal Kesehatan Holistic, 2018)
The role of nurse medical surgical specialist is as caregiver, researcher, and innovator applied on nursing care of cancer patients that used the chronic illness trajectory model approach, application of evidence based nursing practise in spiritual care program on leukemia patients to reduce depression, and perform innovation group project on educational management for patients undergoing radioactive Iodine 131 in Radioactive Isolation Ward Dharmais Cancer Hospital. The trajectory concept is one of the nursing theories that assist patients and caregivers’ empowerment to provide appropriate care in the stage and phase of patient's illness and focuses on palliative care. Palliative care is one of the focus areas of nurse specialist in the field of cancer care that will improve the patient's independence and quality of life. The application of spiritual care program is non-invasive, cheap, safe, and practically in managing the patient's depression status. Education could improve patients' understanding of radiotherapy and its side effects to improve the quality of nursing care